Pengaruh Jumlah Bagi Hasil Deposito, Likuiditas, Dan Inflasi Terhadap Jumlah Deposito Mudharabah Pada Bank Muamalat Indonesia Periode 2013-2017 - Murniati (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This research is a study on Regional Original Revenue, General Allocation Funds, Special Allocation Funds, and Revenue Sharing Funds on economic growth in Indonesia. This research takes the title: "The Effect of Regional Original Revenue, General Allocation Fund, Special Allocation Fund, and Revenue Sharing Fund on economic growth in Indonesia in 2013-2017. The purpose of this study was to determine the effect of Regional Original Revenues, General Allocation Funds, Special Allocation Funds, and Revenue Sharing Funds on economic growth in Indonesia.The population in this study is all data from the Original Regional Revenue, the General Allocation Fund, the Special Allocation Fund, and the Profit Sharing Fund in Indonesia. The method used in sampling is purposive sampling. The number of samples taken in this study are Regional Original Revenues, General Allocation Funds, Special Allocation Funds, and 29 provincial Revenue Sharing Funds from 2013-2017.Based on the results of research and data analysis using multiple linear regression analysis shows that: (1) Regional Original Revenue influences economic growth, (2) General Allocation Fund does not affect economic growth, (3) Special Allocation Fund does not affect economic growth, (4) Revenue Sharing Funds do not affect economic growth, (5) Regional Own Revenues, General Allocation Funds, Special Allocation Funds, and Revenue Sharing Funds together affect economic growth.